Changes in liver enzymes in patients infected with the dengue virus (Research, Society and Development, 2024)
This investigation aims to present the results of an analysis of changes in the liver enzymes AST, ALT, and GGT in patients with dengue admitted to a teaching hospital in the western region of Paraná. A retrospective analysis of electronic medical records of patients admitted between January 2023 and June 2024 was conducted, where the results of hepatic enzyme dosages were collected, along with other variables. Enzyme elevations were distributed similarly between sexes, with no clear predominance. The age-based analysis showed an increase in ALT especially in adults, while children and the elderly displayed elevated AST levels. The classification into risk groups revealed a progressive increase in AST and ALT levels in the more severe groups, particularly in groups C and D, which included ICU patients and cases that progressed to death. Among the 310 patients analyzed, 80.32% presented elevated AST, without statistical significance for severity (p = 0.14), while 36.77% showed ALT above reference values, significantly correlated with greater severity (p < 0.001). GGT had a limited sample but was elevated in 61.11% of cases evaluated. These results support the hypothesis that there are alterations in hepatic enzymes in dengue patients admitted to the teaching hospital. The significant elevation of ALT suggests its usefulness as a marker of infection severity, while AST and GGT require further investigation to elucidate their role in dengue-associated hepatic complications.